2020
DOI: 10.1007/s10157-020-01886-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between eosinophilia and renal prognosis in patients with pathologically proven cholesterol crystal embolism

Abstract: Background Approximately, 20-70% of patients with cholesterol crystal embolism (CCE) have eosinophilia. However, it remains unknown how eosinophilia influences renal prognosis in patients with CCE. In this study, we investigated the association between eosinophil count (Eo) and renal prognosis in CCE patients on steroid therapy. Methods The present study is a single-centered retrospective cohort study in patients with renal dysfunction and CCE from April 2007 to May 2018. This study included the patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Various systemic disorders affecting kidney function, such as cholesterol embolization syndrome (CES), may be accompanied by eosinophilia [19,20]. Generally, the incidence of eosinophilia in patients with CES ranges from 14-71% [21]. Patients with CES with kidney involvement showed an even greater increase in the eosinophilic granulocyte count [22], suggesting a potential link between eosinophilic granulocytes and the kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various systemic disorders affecting kidney function, such as cholesterol embolization syndrome (CES), may be accompanied by eosinophilia [19,20]. Generally, the incidence of eosinophilia in patients with CES ranges from 14-71% [21]. Patients with CES with kidney involvement showed an even greater increase in the eosinophilic granulocyte count [22], suggesting a potential link between eosinophilic granulocytes and the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic granulocytes are activated by in ammatory mediators such as interleukin (IL)-3 and IL-5, which increase their circulation for approximately 18-24 h before migrating from the blood vessels. The mechanisms of the damage caused by eosinophilic granulocytes include: 1) the release of particulate products such as alkaline proteins, which can damage epithelial tissue and cause in ammation, and 2) the release of platelet-activating factor, cytokines, and chemokines, further triggering tissue remodeling and brosis [21,27]. Makiya et al [28] observed a correlation between the eosinophilic granulocyte count and CD69 and granule protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol crystal embolism (CCE) has also been associated with peripheral eosinophilia. It has been found in some studies that around 20-70% of patients with CCE have peripheral eosinophilia [53][54][55].…”
Section: Cholesterol Crystal Embolismmentioning
confidence: 99%
“…In a relatively recent case-control study by Tariq et al [ 110 ], they demonstrated that peripheral eosinophilia is an independent predictor of tissue eosinophilia and subsequent progression to end-stage kidney disease. Given that ∼20–70% of cholesterol crystal embolism patients present eosinophilia [ 111 , 112 , 113 , 114 , 115 , 116 ], Mochida et al [ 117 ] demonstrated in a single-centered cohort study that eosinophilia served as a prognostic factor for renal death among cholesterol crystal embolism patients. Besides, Gauckler and colleagues [ 118 ] also reviewed acute or chronic kidney diseases and other special condition associated with eosinophilia.…”
Section: Eosinophils In Kidney Disordersmentioning
confidence: 99%